A method for variable pressure load estimation in spur and helical gear pumps. (August 2016) - Battarra, M.; Mucchi, E.
Abstract: A systematic procedure is proposed to determine variable excitation loads coming from pressure evolution inside tooth spaces in external gear pumps. Pressure force and torque are estimated with respect to the angular position of the gears, taking into account the phenomena that occur during the meshing course. In particular, the paper proposes a general methodology aiming at determining pressure force and torque components along the three coordinate axes and suitable to be applied on both spur and helical gear configuration. Firstly, the method to calculate pressure loads acting on a single tooth space during a complete revolution is given, then the total pressure force and torque loading each gear is obtained. Particular attention is addressed on the description of the helical gear scenario. As an example, the method is applied to a tandem gear pump, characterized by the presence of two stages, one with spur gears and one with helical gears. An experimentally assessed model to calculate the pressure ripple inside the tandem pump is described and the proposed procedure for pressure load estimation is applied. Eventually, the pressure loads estimated with the present procedure are compared with other estimation methods already described in the literature. The comparison shows that the present methodology is able to describe a wider range of phenomena involved in the meshing evolution and to determine all the pressure force and torque components applied to helical gears. The method gives suitable results to study the balancing and the dynamic behavior of gear pumps. Highlights: We propose a novel method for load estimation in gear pumps. Analytical determination of variable pressure excitation. The method is assessed via a tandem gear pump dynamic model.